2016
DOI: 10.3109/03602532.2016.1151037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical determinants of calcineurin inhibitor disposition: a mechanistic review

Abstract: The calcineurin inhibitors (CNIs) tacrolimus and cyclosporine are widely used immunosuppressive drugs characterized by high pharmacokinetic and pharmacodynamic variability, both between and within patients. CNIs are highly lipophilic, poorly soluble, undergo extensive first-pass metabolism and are cleared by the liver. In both gut and liver, CNIs are substrates for the cytochrome P450 (CYP) enzymes 3A4 and 3A5 as well as the P-glycoprotein (P-gp) transporter, whose functions are determined by a complex interpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
169
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(180 citation statements)
references
References 301 publications
0
169
0
Order By: Relevance
“…105 Expressers of the CYP3A5 enzyme (as is more often the case in black and Asian patients) do require higher dosages to reach therapeutic tacrolimus exposure. [105][106][107] The recently developed prolonged-release formulation in tablet form (also known as LCP-tacrolimus) is released and absorbed more distally in the gut. 105,106 This newer formulation of prolonged-release tacrolimus in tablets has shown some differences in terms of pharmacokinetics but longterm clinical outcome data is yet to be established.…”
Section: Strategies For Managing Nonadherencementioning
confidence: 99%
See 2 more Smart Citations
“…105 Expressers of the CYP3A5 enzyme (as is more often the case in black and Asian patients) do require higher dosages to reach therapeutic tacrolimus exposure. [105][106][107] The recently developed prolonged-release formulation in tablet form (also known as LCP-tacrolimus) is released and absorbed more distally in the gut. 105,106 This newer formulation of prolonged-release tacrolimus in tablets has shown some differences in terms of pharmacokinetics but longterm clinical outcome data is yet to be established.…”
Section: Strategies For Managing Nonadherencementioning
confidence: 99%
“…[105][106][107] The recently developed prolonged-release formulation in tablet form (also known as LCP-tacrolimus) is released and absorbed more distally in the gut. 105,106 This newer formulation of prolonged-release tacrolimus in tablets has shown some differences in terms of pharmacokinetics but longterm clinical outcome data is yet to be established. 106 After absorption, tacrolimus diffuses extensively in blood cells and tissues.…”
Section: Strategies For Managing Nonadherencementioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Pharmacokinetics After oral administration, tacrolimus undergoes extensive first-pass effects via p-glycoprotein and intestinal and hepatic cytochrome P450 3A (CYP3A) enzymes. 10 Tacrolimus is primarily eliminated from the body in the bile by hepatic metabolism, and less than 1% of unchanged drug is excreted in the urine. 11 The oral bioavailability of tacrolimus is low and exhibits large intra-and interindividual variability, ranging from 4% to 89% (mean around 25% in liver and RT recipients and in patients with renal impairment).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…The authors presume that the identified sets of gene variants (because of their distribution with oxidoreductase/monooxygenase activity) are causally linked to tacrolimus metabolism and thus exposure. It is important to note, however, that in the first 3 mo after transplantation, a number of clinical factors known to affect tacrolimus bioavailability closely covary with tacrolimus dosing and influence dose-corrected exposure, for example, graft function or dysfunction, gastrointestinal motility, hematocrit, albumin, corticosteroid tapering, and concomitant drugs (drug-drug interactions) (2). The fact that these factors were not corrected for increases the risk of overfitting the PLS1 models by modeling variability that is likely to be determined by clinical factors.…”
Section: To the Editormentioning
confidence: 99%